A new emergency during the latest phase of the COVID-19 pandemic: access to healthcare services by patients with non-communicable diseases - De Sarro, Caterina; Papadopoli, Rosa; Morgante, Maria Carmela; Pileggi, Claudia (Frontiers in Medicine, 2023)
Background: the aim of our study was to investigate the impact of the COVID-19 pandemic on the healthcare and the disease management of patients affected by non-communicable diseases (NCDs), by exploring, specifically, the obstacles encountered in the access to healthcare services during the latest phase of the pandemic.This cross-sectional study was carried out among subjects attending the anti-SARS-CoV2 vaccination clinic in a Teaching Hospital of Southern Italy. To be included in the study, subjects had to be affected by at least one NCD, such as diabetes, hypertension, respiratory and heart diseases, renal and liver chronic conditions, immunodeficiency disorders due to cancer, or being kidney or liver transplant recipients.Results: Among the 553 subjects who completed the questionnaire, the 39.4% (95% IC=35.3-43.6) experienced obstacles in the access to healthcare services in the six months prior to the enrollment. The most frequent cancelled/postponed healthcare services were the visits for routine checks for NCDs (60.6%, 95% IC=53.9-67), control visits of more complex diseases as cancer or transplantation (17.3%, 95% IC=12.6-22.8),) and scheduled surgery (11.5%, 95% IC=7.7-16.4). The patients who experienced canceled/postponed healthcare services were significantly more likely to suffer from 3 or more NCDs (p=0.042), to be diabetics (p=0.038), to have immunodeficiency disorders (p=0.028) and to have consulted GP at least once (p=0.004).Our results appear to be fundamental for guiding the choices of providers in order to concentrate organizational efforts to recover and reschedule missed appointments, where applicable, of the most fragile patients by virtue of age and chronic conditions.